Comparison of the Susceptibilities of Candida spp. to Fluconazole and Voriconazole in a 4-Year Global Evaluation Using Disk Diffusion - (:unkn) unknown (My University, 2003)
ABSTRACT From June 1997 to December 2001, results of in vitro susceptibility tests of yeast isolates from 35 countries were collected. For 2001 alone, fluconazole results were reported for 22,111 yeast isolates from 77 institutions in 30 countries. Of these isolates, 18,569 were also tested for susceptibility to voriconazole. All study sites tested clinical yeast isolates by recently endorsed NCCLS disk diffusion method M44-P. Disk test plates were automatically read and results were recorded with the BIOMIC Image Analysis System. Species, drug, zone diameter, susceptibility category, MIC, and quality control results were electronically submitted by e-mail quarterly for analysis. Duplicate test results (same patient and same species with same sensitivity-resistance profile and biotype results during any 7-day period) and uncontrolled test results were eliminated from this analysis. The proportion of Candida albicans isolates decreased from 69.7% in 1997 to 1998 to 63.0% in 2001, and this decrease was accompanied by a concomitant increase in C. tropicalis and C. parapsilosis . The susceptibility (susceptible [S]or susceptible-dose dependent [S-DD]) of C. albicans isolates to fluconazole was virtually unchanged, from 99.2% in 1997 to 99% in 2001; the C. glabrata response to fluconazole was unchanged, from 81.5% S or S-DD in 1997 to 81.7% in 2001, although the percentage of resistant isolates from blood and upper respiratory tract samples appeared to increase over the study period; the percentage of S C. parapsilosis isolates decreased slightly, from 98% S or S-DD in 1997 to 96% in 2001; and the percentage of S isolates of C. tropicalis increased slightly, from 95.7% in 1997 to 96.9% in 2001. The highest rate of resistance to fluconazole among C. albicans isolates was noted in Ecuador (7.6%, n = 250). Results from this investigation indicate that the susceptibility of yeast isolates to fluconazole has changed minimally worldwide over the 4.5-year study period and that voriconazole demonstrated 10- to 100-fold greater in vitro activity than fluconazole against most yeast species.